Model Pendampingan Pastoral bagi Remaja Korban Cyberbullying: Studi di Jemaat GPM Rehobot dan Jemaat GPM Bethel Kota Ambon - Ruimassa, Aleta Apriliana; Pieter, Jenne Jessica Revanda; Patty, Martha Marselina; Nanuru, Ricardo Freedom (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to understand the impact of cyberbullying and to develop a pastoral assistance framework for teenagers who are victims of cyberbullying in the GPM Bethel and GPM Rehoboth congregations. To address the research problem, the researcher employed a qualitative research method. Observations were conducted on the impact of cyberbullying on teenagers in the GPM Bethel and GPM Rehoboth congregations, interviews were held with victims, church council members, and youth mentors in both congregations, and document studies related to cyberbullying and pastoral care were carried out. The findings reveal that in the GPM Bethel and GPM Rehoboth congregations, 57 teenagers have experienced cyber violence. Through Focus Group Discussions (FGDs), it was further found that 33 teenagers from the GPM Bethel congregation and 24 from the GPM Rehoboth congregation had been victims of cyberbullying while using WhatsApp, Instagram, Facebook, and online games as platforms for communication and building friendships. The hope of finding understanding and supportive peers through these platforms had, unfortunately, led to hurtful actions among the teenagers. The study highlights the need for a pastoral care approach to assist victims in recovering and developing healthy ways of building social relationships while addressing the trauma caused by cyberbullying.